Genomic profiling of WRKY transcription factors and functional analysis of CcWRKY7, CcWRKY29, and CcWRKY32 related to protoberberine alkaloids biosynthesis in Coptis chinensis Franch - Huang, Xiaoqiang; Jia, An; Huang, Tao; Wang, Li; Yang, Guohua; Zhao, Wanli (Frontiers in Genetics, 2023)
Coptis chinensis (Huanglian in Chinese) is an important economic crop with medicinal value. Its rhizome has been used as a traditional herbal medicine for thousands of years in Asia. Protoberberine alkaloids, as the main bioactive component of C. chinensis, have a series of pharmacological activities. However, the protoberberine alkaloids content of C. chinensis is relatively low. Understanding the molecular mecha-nisms affecting the transcriptional regulation of protoberberine alkaloids would be crucial to increase their production via metabolic engineering. WRKY, one of the largest plant-specific gene families, regulates plant defense responses via the biosynthesis of specialized metabolites such as alkaloids. Totally, 41 WRKY transcription factors (TFs) related to protoberberine alkaloid biosynthesis were identified in the Coptis chinensis genome and classified into three groups based on phylogenetic and conserved motif anal-yses. Three WRKY genes (CcWRKY7, CcWRKY29, and CcWRKY32) may regulate protoberberine alkaloid biosynthesis, as suggested by gene-specific expression patterns, metabolic pathways, phylogenetic, and dual-luciferase analysis. Furthermore, the CcWRKY7, CcWRKY29, and CcWRKY32 proteins were spe-cifically detected in the nucleus via subcellular localization. This study provides a basis for understanding the regulatory mechanisms of protoberberine alkaloid biosynthesis and valuable information for breeding C. chinensis varieties.